Pola terapi antihipertensi dan luaran klinis pada preeklamsia - Nela Puspa Tama; Dedy Almasdy; Yelly Oktavia Sari (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Preeclampsia remains a leading cause of maternal and perinatal morbidity and mortality worldwide, necessitating effective clinical management strategies to improve pregnancy outcomes. Despite established guidelines for antihypertensive therapy in pregnancy, data on real-world treatment patterns and their associated clinical outcomes in Indonesian healthcare settings remain limited. Objective: This study aimed to describe sociodemographic and clinical characteristics, antihypertensive therapy patterns, blood pressure changes, and maternal and neonatal outcomes among preeclampsia patients at a tertiary referral hospital in West Sumatra, Indonesia. Methods: A descriptive observational study was conducted involving 80 preeclampsia patients hospitalized at Dr. M. Djamil General Hospital, Padang, from January to December 2025. Data were collected retrospectively from medical records using total sampling based on predefined inclusion and exclusion criteria. The study evaluated sociodemographic characteristics, antihypertensive therapy regimens, blood pressure changes (pre- and post-therapy), and clinical outcomes including maternal symptom resolution and neonatal status. Data were analyzed using descriptive statistics and Wilcoxon signed-rank tests with SPSS version 25. Results: The majority of patients were aged 20–35 years (70%), housewives (72.5%), and had completed senior high school education (61.3%). Methyldopa was the most frequently used oral monotherapy (22.5%), while the combination of methyldopa and nifedipine was the predominant regimen (68.8%). Antihypertensive therapy significantly reduced systolic blood pressure from 168.94 ± 21.21 mmHg to 134.74 ± 13.32 mmHg and diastolic blood pressure from 104.84 ± 13.80 mmHg to 83.11 ± 7.11 mmHg (p < 0.001). Maternal symptoms including headache and blurred vision resolved completely following treatment. However, neonatal outcomes remained concerning, with 35.0% of newborns requiring NICU admission and 16.3% resulting in intrauterine fetal death. Fetal complications including oligohydramnios (12.5%) and absent end-diastolic flow (2.5%) indicated impaired uteroplacental perfusion. Conclusion: Antihypertensive therapy effectively reduced blood pressure and improved maternal symptoms in preeclampsia patients. However, the persistence of adverse neonatal outcomes despite maternal hemodynamic improvement underscores the need for comprehensive management approaches that include close maternal-fetal monitoring, early detection of placental insufficiency, and optimized referral systems. Further prospective studies with larger sample sizes and extended follow-up are warranted to evaluate long-term therapeutic outcomes.